Mechanisms and regulations of ferroptosis - Zhang, Xu-Dong; Liu, Zhong-Yuan; Wang, Mao-Sen; Guo, Yu-Xiang; Wang, Xiang-Kun; Luo, Kai; Huang, Shuai; Li, Ren-Feng (Frontiers in Immunology, 2023)
Regulation of cell mortality for disease treatment has been the focus of research. Ferroptosis is an iron-dependent regulated cell death whose mechanism has been extensively studied since its discovery. A large number of studies have shown that regulation of ferroptosis brings new strategies for the treatment of various benign and malignant diseases. Iron excess and lipid peroxidation are its primary metabolic features. Therefore, genes involved in iron metabolism and lipid metabolism can regulate iron overload and lipid peroxidation through direct or indirect pathways, thereby regulating ferroptosis. In addition, glutathione (GSH) is the body's primary non-enzymatic antioxidants and plays a pivotal role in the struggle against lipid peroxidation. GSH functions as an auxiliary substance for glutathione peroxidase 4 (GPX4) to convert toxic lipid peroxides to their corresponding alcohols. Here, we reviewed the researches on the mechanism of ferroptosis in recent years, and comprehensively analyzed the mechanism and regulatory process of ferroptosis from iron metabolism and lipid metabolism, and then described in detail the metabolism of GPX4 and the main non-enzymatic antioxidant GSH in vivo.